Surface production fuels deep heterotrophic respiration in northern peatlands. Issue 4 (3rd December 2013) - Elizabeth Corbett, J.; Burdige, David J.; Tfaily, Malak M.; Dial, Angela R.; Cooper, William T.; Glaser, Paul H.; Chanton, Jeffrey P.
<x xml:space="preserve">Abstract</x> [1] Multiple analyses of dissolved organic carbon (DOC) from pore waters were conducted to define the processes that govern carbon balance in peatlands: (1) source, reactivity, and transport of DOC with respect to vegetation, peat, and age of carbon substrate, (2) reactivity of DOC with respect to molecular size, and (3) lability to photoxidation of surficial DOC. We found that surface organic production fuels heterotrophic respiration at depth in advection‐dominated peatlands, especially in fens. Fen DOC was Δ14C enriched relative to the surrounding fen peat, and fen respiration products were similar to this enriched DOC indicating that DOC was the main microbial substrate. Bog DOC was more variable showing either enrichment in ∆14C at depth or ∆14C values that follow peat values. This variability in bogs is probably controlled by the relative importance of vertical transport of labile carbon substrates within the peat profile versus DOC production from bog peat. These results extended our set of observations to 10 years at one bog‐fen pair and add two additional bog‐fen pairs to our series of observations. Anaerobic incubations of peat, rinsed free of residual DOC, produced DOC and respiration products that were strikingly similar to the peat values in a bog and two fens. This result demonstrated conclusively that downward advection is the process responsible for the presence of modern DOC found at depth in the peat column. Fen DOC has lower C/N values and up to twice as much LMW (<1 kDa) DOC as bogs due to differences in organic inputs and greater microbial processing. Fluorescence irradiation experiments showed that fen DOC is more photolabile than bog DOC.